Airborne Outreach: Building HIV Capacity and Strengthening Health Care Systems in Rural Botswana. (March 2014) - Reid, Michael J. A.; Haverkamp, Miriam; McAllister, Tammi; Miller, Jonathan; Kirk, Brianna L.
There is a paucity of research demonstrating how HIV-funded services in Africa have improved equity and access to non-HIV services for both HIV-infected and uninfected patients. In this short communication, we describe the impact of an airborne outreach program to provide HIV services to high-HIV burden health facilities in rural Botswana. The analysis demonstrates how this HIV-funded program enhanced access to essential subspecialist services at several rural health facilities across Botswana.